2019
DOI: 10.1177/0046958019861257
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Outcomes and Indicators as a New Challenge in Health Services Research: A Systematic Scoping Review

Abstract: The aim of this systematic scoping review was to identify and analyze indicators that address implementation quality or success in health care services and to deduce recommendations for further indicator development. This review was conducted according to the Joanna Briggs Manual and the PRISMA Statement. CINAHL, EMBASE, MEDLINE, and PsycINFO were searched. Studies or reviews published between August 2008 and 2018 that reported monitoring of the quality or the implementation success in health care services by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…Notable efforts to identify robust implementation outcome instruments at scale include systematic reviews of quantitative instruments validated in mental health settings [13] and public health and community settings [14], and more recently, a systematic scoping review has identified implementation outcomes and indicator-based implementation measures [15]. The vast majority of implementation outcome instruments are developed to assess the implementation of a specific intervention; therefore, a review of implementation outcome instruments validated in physical healthcare settings will retrieve a different set of instruments to those validated in mental health or community settings.…”
Section: Introductionmentioning
confidence: 99%
“…Notable efforts to identify robust implementation outcome instruments at scale include systematic reviews of quantitative instruments validated in mental health settings [13] and public health and community settings [14], and more recently, a systematic scoping review has identified implementation outcomes and indicator-based implementation measures [15]. The vast majority of implementation outcome instruments are developed to assess the implementation of a specific intervention; therefore, a review of implementation outcome instruments validated in physical healthcare settings will retrieve a different set of instruments to those validated in mental health or community settings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, common statements/ recommendations of ADA together with EASD have been published (Inzucchi et al 2012;Rydén et al 2013). Unified quality standards are necessary for a systematic evaluation and reporting of diabetes management programs (Pajunen et al 2010a;Willmeroth et al 2019). Nevertheless, it is unclear if the needs of people with diabetes are finally met.…”
Section: Discussionmentioning
confidence: 99%
“…According to Proctor et al [32], acceptability should be assessed from participant and/or provider perspectives, considering either knowledge of or direct experience with various dimensions of the practice, or in this case, the measures, implemented. The literature supports both quantitative and qualitative methods of assessing healthcare implementation outcomes, including acceptability [28,34,35]. Further, acceptability can be assessed prospectively (before implementation), concurrently (during implementation), and retrospectively (after implementation) [35].…”
Section: Methodsmentioning
confidence: 98%
“…The assessment of employment support program success and individual employment readiness is often based on the use of participant skill assessments developed for use with neurotypical populations. While numerous measures have been developed and validated to evaluate employment readiness and life skills, many of these, including career-planning and employment readiness measures, have not yet been assessed for use with persons on the spectrum [28,29]. The Work Readiness Inventory (WRI) and Ansell-Casey Life Skills Assessment (ACLSA) are two valid and reliable measures of employment readiness and life skills which were developed for use in neurotypical populations [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation